Influence of generics in prescribing dynamics of proton pump inhibitors in general practice - Cammarota, Simona; Citarella, Anna; Menditto, Enrica; De Portu, Simona; Napoli, Luigi; Laringe, Matteo; Sarnelli, Giovanni; Arpino, Giovanni; Piccinocchi, Gaetano; Cuomo, Rosario (Farmeconomia. Health economics and therapeutic pathways, 2009)
Use of antisecretory drugs has greatly increased in recent years in Italy. After the launching of generic lansoprazole (early 2006), several Italian Regional Health Authorities have introduced measures to favour the prescription of less expensive PPI. The aim of this study is to evaluate general practitioners’ prescription (GPs) of different Proton Pump Inhibitors (PPIs) in the period between 2005 to 2008. Analysis has been performed on a database of 99 medical practitioners that have managed an average of 150,000 inhabitants. We evaluate the PPIs prescriptions from Jan 2005 to Dec 2008. Evaluations performed are the following: 1) PPI prescription (total and separately for lansoprazole, esomeprazole, pantoprazole, rabeprazole, and omeprazole); 2) prevalence of the reimbursement purpose (Gastroprotection – G; Acid-Related Disease – ARD); 3) PPI prescriptions separately for ARD diagnostic codes. Data were expressed as Compound Annual Growth Rate (CAGR). PPI consumption were quantified using Defined Daily Dose system (DDD). The total volume of PPI’s prescribing increased progressively over the 4 years (CAGR +15%). The proportion of defined daily doses accounted for by lansoprazole increased from 12.0% in 2005 to 30.9% in 2008. The prescription of omeprazole decreased from 42.2% to 26.7%, while that of esomeprazole remained costant. The reimbursement purpose was higher for G (CAGR +43%) than for ARD (CAGR +7%). We found an increase of lansoprazole prescriptions especially for heartburn (CAGR +52.4%), gastroesophageal reflux (CAGR 34,5%) and upper abdominal pain (CAGR 37,2%). Generic PPIs has unexpectedly increased the prescription of whole drug class during the period 2005-2008. Our data suggest that the appropriateness of PPI prescription after generic PPI introduction should be carefully monitored to distinguish between cost-effective from cost-ineffective PPI treatment.